2015
DOI: 10.1155/2015/746592
|View full text |Cite
|
Sign up to set email alerts
|

The Albedo of Pervious Cement Concrete Linearly Decreases with Porosity

Abstract: Pervious pavements have been advocated as a potential countermeasure to the urban heat island effect. To understand if pervious pavements stay cooler than conventional pavements, the albedo of the pervious concrete must be understood. This study measured the albedo of pervious concrete with different porosity. Four Portland cement concrete mixes were casted, using designed amounts of sand to vary the porosity of the pervious concrete samples. The samples were sliced and the spectral reflectance and albedo of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Albedo is the ratio of the reflected radiant flux to the incident solar radiant flux, which characterizes the ability of the pavement to absorb and reflect solar radiation [8]. Albedo and coefficient of thermal storage were calculated according to the references [9,11,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albedo is the ratio of the reflected radiant flux to the incident solar radiant flux, which characterizes the ability of the pavement to absorb and reflect solar radiation [8]. Albedo and coefficient of thermal storage were calculated according to the references [9,11,18].…”
Section: Methodsmentioning
confidence: 99%
“…Because PPCC have more air void content than traditional PCC, there are obvious differences between them. Studies 2 Advances in Materials Science and Engineering by Haselbach et al and Zhang et al have shown that PPCC has rougher surface and lower albedo than traditional PCC pavement, so that PPCC can absorb more solar radiation [10,11]. Kevern et al collected temperature data of pervious pavement and traditional pavement at different depths, respectively, and found that the temperature at middlelevel (8 cm below the surface) in both concrete types was always higher than the air temperature.…”
Section: Introductionmentioning
confidence: 99%
“…First, there are limited reported on the reflectance of pervious concrete [18,74]. The rough of pervious surface makes its albedo less than normal concrete and thus absorbs more solar irradiation [18,74].…”
Section: Pervious Paver Pervious Cement Concretementioning
confidence: 99%
“…First, there are limited reported on the reflectance of pervious concrete [18,74]. The rough of pervious surface makes its albedo less than normal concrete and thus absorbs more solar irradiation [18,74]. Haselbach and Boyer [18] found the solar reflectance index of pervious concrete pavement is 14 but that of traditional concrete pavement is 37.…”
Section: Pervious Paver Pervious Cement Concretementioning
confidence: 99%
“…Compared to conventional concrete pavements, pervious concrete pavements have lower reflectivity, heat volumetric capacity, thermal conductivity, and absorb additional heat. The reflectivity of pervious concrete determines the reflectivity of aggregates, binders, and voids [12,67]. The higher porosity pavements have a larger surface temperature than lower porosity pavements as they have higher thermal diffusivity, which decreases by porosity increase [62].…”
Section: Contribution Factors To Urban Heat Island Formationmentioning
confidence: 99%